1998
DOI: 10.1037/1064-1297.6.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Associative tolerance to nicotine analgesia in the rat: Tail-flick and hot-plate tests.

Abstract: Previous assessments of associative nicotine tolerance may have confounded associative effects with novelty-induced stress effects, instrumental learning effects, or both. That is, subjects were tested in novel environments, allowed to practice the test response, or both during the tolerance development phase. In the first study, 32 male Sprague-Dawley rats were injected with various doses of nicotine and tested for nociception in the tail-flick and hot-plate tests to assess nicotine's analgesic effects. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 32 publications
2
26
0
1
Order By: Relevance
“…For example, we and others have provided evidence that learning can play an important role in the tolerance which develops rapidly to NIC (see Caggiula et al 1995;Cepeda-Benito et al 1998), and research on other abused drugs indicates that number of drug exposures can be an important factor in dissociating mechanisms of tolerance (Cepeda-Benito and Tiffany 1992).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, we and others have provided evidence that learning can play an important role in the tolerance which develops rapidly to NIC (see Caggiula et al 1995;Cepeda-Benito et al 1998), and research on other abused drugs indicates that number of drug exposures can be an important factor in dissociating mechanisms of tolerance (Cepeda-Benito and Tiffany 1992).…”
Section: Discussionmentioning
confidence: 96%
“…For example, when NIC is repeatedly given in conjunction with predictable environmental stimuli, the resulting tolerance has an important associative component; that is, its manifestation is dependent on the presence of those stimuli. Associative tolerance has been demonstrated for several effects of NIC in rats, including its antinociceptive effects (Caggiula et al 1991(Caggiula et al , 1995Cepeda-Benito et al 1998). The rapid reversibility of associative forms of tolerance, which can be accomplished by administering the drug in the absence of drug-related cues, makes it unlikely that they are dependent on longterm receptor changes in the brain (Siegel 1989;Caggiula et al 1995).…”
Section: Discussionmentioning
confidence: 97%
“…The finding of contextual tolerance after ten but not after 15 and 20 sessions could be interpreted as a spurious result. However, previous research has reported the presence of robust contextual tolerance on the hot plate after eight and 13 conditioning sessions (Cepeda-Benito et al 1998, 2000. For instance, CepedaBenito et al (2000) found that dose-response curve of rats receiving nicotine explicitly paired with the distinctive context was shifted significantly to the right of the doseresponse curve of rats that received nicotine explicitly unpaired with the context.…”
Section: Discussionmentioning
confidence: 96%
“…All solutions (saline and nicotine) were subcutaneously injected in the scruff of the neck (1 ml/kg of body weight). We chose the 1 mg/kg dose of nicotine according to the results of two previous studies in which we determined the doseresponse curve to nicotine in both the tail flick and the hot plate and found evidence of contextual tolerance after eight and 13 conditioning sessions (Cepeda-Benito et al 1998, 2000.…”
Section: Drugsmentioning
confidence: 99%
“…Caggiula and his colleagues have shown that environmental cues mediate tolerance to its anorectic ef-f f fects , its tachycardiac effect (Epstein, Caggiula, Perkins, McKenzie, & Smith, 1991), its cortisone-elevating effect ; but see Davis, Cepeda-Benito, Harraid, & Wellman, 2005), and its analgesic effect (Caggiula et al, 1993;. Cepeda-Benito and colleagues have also found contextual control of the analgesic effect of nicotine (CepedaBenito, Davis, Reynoso, & Harraid, 2005;Cepeda-Benito, Reynoso, & Erath, 2000;Cepeda-Benito, Reynoso, & McDaniel, 1998).…”
mentioning
confidence: 98%